Wood-bamboo Particleboard: Mechanical Properties - De Almeida, Aliane C. [UNESP]; De Araujo, Victor A.; Morales, Elen A. M. [UNESP]; Gava, Maristela [UNESP]; Munis, Rafaele A. [UNESP]; Garcia, Jose N.; Cortez-Barbosa, Juliana [UNESP] (North Carolina State Univ Dept Wood & Paper Sci, 2017)
Mechanical characteristics were evaluated of wood-bamboo-based particleboard having the proportions of 100% wood and 0% bamboo, 75% wood and 25% bamboo, and 50% wood and 50% bamboo. This particleboard used Eucalyptus urophylla x grandis wood, Dendrocalamus asper bamboo, and castor oil-based polyurethane resin. Through destructive testing, the values of perpendicular tensile, static bending, modulus of elasticity, and screw pullout strength in the top and face surfaces were analyzed. For 0%, 25%, and 50% bamboo the values were 1.68 MPa, 1.37 MPa, and 1.4 MPa, respectively, for perpendicular tensile; 15.2 MPa, 17.6 MPa, and 18.5 MPa, respectively, for static bending; 2466 MPa, 2694 MPa, and 2922 MPa, respectively, for modulus of elasticity; 1256 MPa, 1922 MPa, and 1362 MPa, respectively, for screw pullout strength in top; and 1392 MPa, 1342 MPa, and 1414 MPa, respectively, for screw pullout strength in face. These results were superior to those presented by ABNT NBR 14810 (2013) and ANSI 208.1 (1999). After performing a Tukey test at 5%, the values for each treatment did not show a significant difference among them.
Keywords: Eucalyptus urograndis; Dendrocalamus asper; Lignocellulosic Panel; Mechanical Properties